The genetic effects in hybrid lines of tropical corn (Zea mays L.) III. Lodging, uncovered ears and ear rot. - Martínez, Gaspar (2016)
This study report genetic effects for lodging, uncovered ears and ear rot, of 42 single cross hybrids made with seven lines developed in the humid tropic of México, and six lines developed in the dry tropic, using a North Caroline II mating design. Hybrid variation was mainly due to GCA variance, and scanty to SCA variance for all the three attributes, although for ear rot, SCA variance had a considerable role, too. Partitioning GCA variance, revealed humid tropic lines had highest contribution to lodging and ear covering variance, and dry tropic lines the highest contribution to ear rot variance. In addition, humid tropic lines had higher GCAxEnvironment interaction variance than dry tropic lines. In conclusion, GCA effects, which reveal additive genetic variance, were the main effects for all the three attributes, and that GCA effects were higher in humid tropic lines than those of the dry tropic, maybe due to their mobilization in a more ample and diverse region.